Mesophyll conductance in leaves of Japanese white birch (Betula platyphylla var. japonica) seedlings grown under elevated CO2 concentration and low N availability. Issue 4 (16th March 2015) - Kitao, Mitsutoshi; Yazaki, Kenichi; Kitaoka, Satoshi; Fukatsu, Eitaro; Tobita, Hiroyuki; Komatsu, Masabumi; Maruyama, Yutaka; Koike, Takayoshi
Abstract : To test the hypothesis that mesophyll conductance (gm ) would be reduced by leaf starch accumulation in plants grown under elevated CO2 concentration [CO2 ], we investigated gm in seedlings of Japanese white birch grown under ambient and elevated [CO2 ] with an adequate and limited nitrogen supply using simultaneous gas exchange and chlorophyll fluorescence measurements. Both elevated [CO2 ] and limited nitrogen supply decreased area‐based leaf N accompanied with a decrease in the maximum rate of Rubisco carboxylation (Vc, max ) on a CO2 concentration at chloroplast stroma (Cc ) basis. Conversely, only seedlings grown at elevated [CO2 ] under limited nitrogen supply had significantly higher leaf starch content with significantly lower gm among the treatment combinations. Based on a leaf anatomical analysis using microscopic photographs, however, there were no significant difference in the area of chloroplast surfaces facing intercellular space per unit leaf area among treatment combinations. Thicker cell walls were suggested in plants grown under limited N by increases in leaf mass per area subtracting non‐structural carbohydrates. These results suggest that starch accumulation and/or thicker cell walls in the leaves grown at elevated [CO2 ] under limited N supply might hinder CO2 diffusion in chloroplasts and cell walls, which would be an additional cause of photosynthetic downregulation as well as a reduction in Rubisco activity related to the reduced leaf N under elevated [CO2 ].